2020
DOI: 10.3390/pr8121567
|View full text |Cite
|
Sign up to set email alerts
|

Syngas Derived from Lignocellulosic Biomass Gasification as an Alternative Resource for Innovative Bioprocesses

Abstract: A hybrid system based on lignocellulosic biomass gasification and syngas fermentation represents a second-generation biorefinery approach that is currently in the development phase. Lignocellulosic biomass can be gasified to produce syngas, which is a gas mixture consisting mainly of H2, CO, and CO2. The major challenge of biomass gasification is the syngas’s final quality. Consequently, the development of effective syngas clean-up technologies has gained increased interest in recent years. Furthermore, the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 172 publications
0
28
0
Order By: Relevance
“…The conversion of organic solid matter through lignocellulosic gasification into a gaseous mixture of H 2 , CO, CO 2 , and CH 4 is another approach for LB valorization. The obtained synthetic-"syngas"-can be directly used as combustible for energy generation or as feedstock for chemical or biological processes [22]. Strict anaerobes, mostly acetogens, are used for syngas conversion to organic acids, alcohols, and other chemicals by "indirect fermentation"(as in this process, the biomass is previously converted to syngas and only then fed to microorganisms) [22,23].…”
Section: Lignocellulosic Biomass As Raw Materialsmentioning
confidence: 99%
“…The conversion of organic solid matter through lignocellulosic gasification into a gaseous mixture of H 2 , CO, CO 2 , and CH 4 is another approach for LB valorization. The obtained synthetic-"syngas"-can be directly used as combustible for energy generation or as feedstock for chemical or biological processes [22]. Strict anaerobes, mostly acetogens, are used for syngas conversion to organic acids, alcohols, and other chemicals by "indirect fermentation"(as in this process, the biomass is previously converted to syngas and only then fed to microorganisms) [22,23].…”
Section: Lignocellulosic Biomass As Raw Materialsmentioning
confidence: 99%
“…Previous studies reported that 2,3-BDO has been investigated from various strains and many substrates [10,21,23,24,27,28]. Among them, 2,3-BDO research was performed using biodiesel-derived crude glycerol from K. aerogenes ATCC 29007.…”
Section: Improvement Of 23-bdo Production Using Extracted Algal Sugars and Biodiesel-derived Crude Glycerolmentioning
confidence: 99%
“…2,3-BDO, a chemical substance that can be produced by the biomass conversion process through fermentation of microorganisms, has a strong hydrophilic property as a colorless and odorless chiral compound in liquid or crystal form [21][22][23]. Because it has a low freezing point, −60 • C, it can be used as antifreeze.…”
Section: Introductionmentioning
confidence: 99%
“…Syngas, a gas mixture primarily composed of CO, H 2 , and CO 2 , has attracted considerable interest as a raw material for the production of biofuels and biochemicals via anaerobic fermentation processes such as syngas fermentation [ 1 ], microbial chain elongation [ 2 ], hydrogenotrophic methanation [ 3 ], and microbial assisted bioelectrochemical synthesis (BES) for conversion of CO 2 /CO [ 4 ]. Syngas can be generated via gasification of solid fuels such as coal and lignocellulosic biomass, which is an effective way of making use of the recalcitrant lignin present in lignocellulosic biomass [ 5 , 6 ]. In addition, CO is the major byproduct of incomplete combustion of carbonaceous materials such as coal, oil, and petroleum products, and it has been generated and discharged in significant quantities by related sectors such as steel industries [ 7 ].…”
Section: Introductionmentioning
confidence: 99%